(untitled) (Research, Society and Development, 2022)
Objective: to carry out an integrative review on the role of the pharmacist in the reverse logistics of medicines in Brazil. Methods: refers to an integrative literature review on the practice of reverse logistics of unused or expired drugs in the population. Results: it was detected that the country’s sanitary experience has problems in relation to the process of collection, treatment, and disposal of biological and chemical waste, causing a huge impact on public health and the environment. The main disposal sites were common garbage and toilets, and a large part of the population does not intend to seek information about the correct disposal of waste and its possible impacts on the environment. Only 2% of pharmacies and/or drugstores established the use of collectors for the disposal of medicines and/or health products that are no longer in use or expired. Pharmaceutical entrepreneurs are likely to introduce reverse logistics in healthcare facilities. Conclusion: performing the reverse logistics and proper disposal of unused or expired drugs from the general population is an immense challenge. There is a need for collector installations in health establishments, especially in pharmacies and/or drugstores, and the pharmacist needs to take ownership of this issue and be an agent of transformation, not only in the attitude of the population, but as a sensitizer for managers public or private companies under the relevance of reverse logistics in Brazil and in the world.